Pengaruh partikel tersuspensi dari berbagai variabel hidrologi terhadap kualitas air sungai maruni di Kabupaten Manokwari - Adriana, Vivi; Heryanto Langsa, Markus; Afkril, Baina (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: This study aims to analyze the effect of suspended particles (TSS) from various hydrological variables on the water quality of the Maruni River in Manokwari Regency. The method used in this research is quantitative descriptive method. Hydrological variable data includes calculation of erosion rate, Sediment Delivery Ratio (SDR), estimated sediment size and surface water runoff discharge. Water quality is measured based on the physical parameters of particle content/suspended density and turbidity. The sampling method refers to SNI and water sample quality testing was carried out at the University of Pa-pua PPLH Environmental Laboratory. The results showed that the erosion rate value in Maruni watershed was 101.001 (tons/ha/yr) with the category of moderate erosion hazard level. Sediment Delivery Ratio (SDR) of Maruni watershed is 0,15 or 15%. The total value of sediment potential generated is 41757,98 tons/year. The surface water runoff discharge that occurs in the Maruni watershed is 48,11 m3 /second. TSS and turbidity concentrations in hot conditions still meet the National Water Quality Standards, while in rainy conditions at mid to downstream points the TSS concentration ranges from 89 mg/L- 228 mg/L and Turbidity ranges from 76.1 NTU- 237.5 NTU has exceeded the National Water Quality Standards according to Appendix VI of Government Regulation No. 22 of 2021 class B for TSS and Minister of Health Regulation (PERMENKES) No. 32 of 2017 for turbidity. Based on the identification results, recommendations for land and water conservation efforts can be made to reduce the risks that occur and maintain water quality.